Moderating Role of Investment Efficiency between Board Diversity and Dividend Policy: Evidence from Pakistan - Kamran Mohy-Ud-Din; Riaz Ahmad; Hafiz Muhammad Ishaq; Muhammad Akram (iRASD Journal of Management)
The purpose of this study is to enhance the understanding in debate of governance demographics by investigate the impact of board diversity on dividend policy and moderating effect of corporate investment efficiency on dividend policy. The sample incorporated in this study comprises of panel data of 77 firms listed in Karachi stock exchange (KSE) during the period of 2012-2019. This study performs a parametric technique regression analysis to measure the investment efficiency and Panel least square models to investigate the association between board diversity and dividend policy. Furthermore, hierarchical explained the results for interaction effect of investment efficiency. This study adds a new finding in the corporate governance through empirical an investigation on the association between board diversity and dividend policy. Results support the interaction effect of investment efficiency between board diversity and dividend policy. Our study suggests that firms involve in high level of efficient investment with diverse ethnic backgrounds and gender in corporate board significantly associated with dividend policy. This study explains the practical implications for the corporate boards in the south Asian culture who enhance the investment efficiency that main goal of finance to enhance the wealth maximization of shareholders in terms of dividends.